History of pre-eclampsia does not appear to be a risk factor for vascular phenotype in women with systemic sclerosis - Arsène Mekinian; Eric Hachulla; Alain Lescoat; Elisabeth Pasquier; Christian Agard; Sabine Berthier; Perrine Smets; Grégory Pugnet; Emmanuel Chatelus; Marie-Elise Truchetet; Viviane Queyrel; Nathalie Tieulie; et al. (RMD Open)
Background Vascular phenotype is associated with a poor prognosis in systemic sclerosis (SSc). The identification of its risk factors could facilitate its early detection.Objectives To explore risk factors for a vascular phenotype of SSc, among them a history of pre-eclampsia.Methods This observational multicentre case–control study enrolled adult women fulfilling European Alliance of Associations for Rheumatology 2013 diagnosis criteria for SSc and having a pregnancy history≥6 months before SSc diagnosis in 14 French hospital-based recruiting centres from July 2020 to July 2022. Cases had specific vascular complications of SSc defined as history of digital ischaemic ulcers, pulmonary arterial hypertension, specific cardiac involvement or renal crisis. Women with SSc were included during their annual follow-up visit and filled in a self-administered questionnaire about pregnancy. A case report form was completed by their physician, reporting data on medical history, physical examination, clinical investigations and current medication. The main outcome was the presence/absence of a personal history of pre-eclampsia before SSc diagnosis, according to the validated pre-eclampsia questionnaire.Results 378 women were included: 129 cases with a vascular phenotype and 249 matched controls. A history of pre-eclampsia was reported in 5 (3.9%) cases and 12 (4.8%) controls and was not associated with a vascular phenotype (OR=0.96, 95% CI 0.28 to 3.34, p=0.9). Besides, Rodnan skin score and disease duration≥5 years were risk factors for vascular phenotype.Conclusions In women with SSc and a pregnancy history≥6 months before SSc, a history of pre-eclampsia is not associated with a vascular phenotype.